PARENT‐TEACHER RELATIONSHIPS IN ELEMENTARY SCHOOL: AN EXAMINATION OF PARENT‐TEACHER TRUST. Issue 10 (21st October 2016) - Santiago, Rachel T.; Garbacz, S. Andrew; Beattie, Tiffany; Moore, Christabelle L.
Abstract : Trust is an important dimension of parent educational involvement and parent‐teacher relationships. Preliminary research suggests that parent trust in teachers and schools is associated with student learning and behavior. However, examinations of parent trust in children's education are limited. The present study investigated the influence of demographic variables on parent trust and relations among parent trust, student behavior, and parent involvement. Findings suggested that student eligibility for a free or reduced‐price lunch predicted parent trust of teachers and schools, parent trust was correlated with dimensions of student behavior, and parent trust of teachers predicted parent involvement. Implications for parent involvement and parent‐teacher relationships are discussed.